2021
DOI: 10.3390/ijms22136938
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib (STI571) Inhibits the Expression of Angiotensin-Converting Enzyme 2 and Cell Entry of the SARS-CoV-2-Derived Pseudotyped Viral Particles

Abstract: A group of clinically approved cancer therapeutic tyrosine kinase inhibitors was screened to test their effects on the expression of angiotensin-converting enzyme 2 (ACE2), the cell surface receptor for SARS-CoV-2. Here, we show that the receptor tyrosine kinase inhibitor imatinib (also known as STI571, Gleevec) can inhibit the expression of the endogenous ACE2 gene at both the transcript and protein levels. Treatment with imatinib resulted in inhibition of cell entry of the viral pseudoparticles (Vpps) in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A previous study shows that imatinib inhibits SARS-CoV-2 in a luciferase-based pseudoparticle entry assay in Vero E6 cells ( 37 ). Moreover, chronic myeloid leukemia patients treated with imatinib show low numbers of COVID-19 cases ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study shows that imatinib inhibits SARS-CoV-2 in a luciferase-based pseudoparticle entry assay in Vero E6 cells ( 37 ). Moreover, chronic myeloid leukemia patients treated with imatinib show low numbers of COVID-19 cases ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that amuvatinib efficiently blocked SARS-CoV-2 replication with no cytopathic effect in Vero E6 cells. Previous study shows that imatinib, another tyrosine kinase inhibitor, blocks SARS-CoV-2 infection by reducing the expression of ACE2 ( 37 ). Here, we showed that not only imatinib, but also amuvatinib, displayed antiviral activity against SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin is an autophagy activator, and its anti-inflammatory action is explained by the inhibition of the NF-κB proinflammatory signalling pathway [27,28]. Also, tyrosine kinase inhibitor (imatinib) has also been recognized as a potent inhibitor of NF-κB signalling and inflammation in vivo and in vitro [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vitro study conducted by Lin et al showed that imatinib can effectively prevent SARS‐CoV‐2 infection with low toxicity. 73 Morales‐Ortega et al 40 in a study monitored the COVID‐19 patients treated with imatinib. Seventeen of 20 patients recovered and three patients died.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhao et al 41 indicated that imatinib had no inhibitory effect on SARS‐CoV‐2 infection. A recent in vitro study conducted by Lin et al showed that imatinib can effectively prevent SARS‐CoV‐2 infection with low toxicity 73 . Morales‐Ortega et al 40 in a study monitored the COVID‐19 patients treated with imatinib.…”
Section: Discussionmentioning
confidence: 99%